Visualizing Cardiac Motion Using Subcutaneously Measured Electrocardiography and Three-Axis Acceleration: Day-to-Day Comparability and Event-Related Changes in Congestive Heart Failure Patients - Wetterling, Friedrich (My University, 2025)
Continuous monitoring of cardiac motion offers valuable insights into heart failure (HF) progression and management. This study explores a method to visualize heart motion trajectories from a novel subcutaneous sensor by integrating electrocardiogram (ECG) data with data from a three-axis accelerometer. By analysing the area covered by those trajectories during the systolic phase changing cardiac function may be assessed quantitatively. During systole the trajectories clearly showed multi-axial mechanical motion of the contracting chest following the cardiac ejection of blood from the left ventricle into the systemic circulation. Consistent daily trajectory patterns were observed in a stable individual on eight different days as their systolic area covered was comparable in size (0.0140mm2 ± 0.054mm2) and orientation. Four Patients that experienced five congestive heart failure events (CHF) showed a reduced systolic plane prior to clinical deterioration as the systolic trajectory area covered was significantly reduced compared to baseline (0.0061mm2 ± 0.0044mm2 at the event versus 0.0158mm2 ± 0.0096mm2 at baseline, p<0.05). Previous research reported qualitatively similar trajectories in healthy volunteers using non-invasive sensors. Additionally, while devices such as other subcutaneous monitoring implants have been evaluated for monitoring ECG and impedance changes in patients with HF, the potential of subcutaneous three-dimensional acceleration measurements remains unexplored. Our findings suggest that this integrated approach could enhance remote monitoring, early detection of decompensation, and personalized treatment strategies for HF patients.
IEEE Xplore
7th Annual International Conference of the IEEE Engineering in Medicine and Biology Society (EMBC)
PUBLISHED
Copenhagen, Denmark,